Impregnation of bentonite with cellulose as adsorbent of congo red - Monica Theresa; Santa Oktavia Ginting (Science and Technology Indonesia, 2017)
The process of bentonite impregnation with cellulose has been studied. Cellulose extracted from rubber wood and clay from natural bentonite was activated. The impregnation process is performed using thiourea as impregnant agent. The impregnation results were characterized by using FT-IR spectrophotometer then the material was used as congo red dye adsorbent. Factors affecting the adsorption process were studied by kinetic parameters and thermodynamic parameters. The FTIR results indicate the impregnation process was succesfully conducted the characterization by FTIR indicated resources of typical absorption of the hydroxyl (OH) and vibrational (-CH) vibration function groups as specific groups of cellulose Appearing at wave numbers 3464.15 cm-1 and 2368.59 cm-1 from impregnated material. Vibration Si-O-Si and Al-O-Si as bentonite-specific strands groups Appear at 1465.9 cm-1 and 609.51 cm-1 wavenumbers in the impregnated spectra. The adsorption thermodynamic study showed that the adsorption and adsorption capacity of the cellulose-impregnated bentonite adsorbent reached the optimum point at 50 ° C at 43.47 mol / g and energy of 11.62 kJ mol. The optimum enthalpy (ΔH) of cellulose bentonite was 143.13 kJ/mol and the minimum entropy (ΔS) at concentration of 40 mg/L was 0.207 kJ/mol. Keywords: Bentonite, cellulose, impregnation; adsorption; Congo red